The effect of lifelong endurance exercise on cardiovascular structure and exercise function in women. (21st May 2020) - Carrick‐Ranson, Graeme; Sloane, Nikita M.; Howden, Erin J.; Bhella, Paul S.; Sarma, Satyam; Shibata, Shigeki; Fujimoto, Naoki; Hastings, Jeffrey L.; Levine, Benjamin D.
Abstract : Key points: The beneficial effects of sustained or lifelong (>25 years) endurance exercise on cardiovascular structure and exercise function have been largely established in men. The current findings indicate that committed (≥4 weekly exercise sessions) lifelong exercise results in substantial benefits in exercise capacity ( V ̇ O 2 max ), cardiovascular function at submaximal and maximal exercise, left ventricular mass and compliance, and blood volume compared to similarly aged or even younger (middle‐age) untrained women. Endurance exercise training should be considered a key strategy to prevent cardiovascular disease with ageing in women as well as men. Abstract: This study was a retrospective, cross‐sectional analysis of exercise performance and left ventricular (LV) morphology in 70 women to examine whether women who have performed regular, lifelong endurance exercise acquire the same beneficial adaptations in cardiovascular structure and function and exercise performance that have been reported previously in men. Three groups of women were examined: (1) 35 older (>60 years) untrained women (older untrained, OU), (2) 13 older women who had consistently performed four or more endurance exercise sessions weekly for at least 25 years (older trained, OT), and (3) 22 middle‐aged (range 35–59 years) untrained women (middle‐aged untrained, MU) as a reference control for the appropriate age‐related changes. Oxygen uptake ( V ̇ O 2 ) and cardiovascular function (cardiac output ( Q ̇ ); stroke volume (SV) acetylene rebreathing) were examined at rest, steady‐state submaximal exercise and maximal exercise (maximal oxygen uptake, V ̇ O 2 max ). Blood volume (CO rebreathing) and LV mass (cardiac magnetic resonance imaging), plus invasive measures of static and dynamic chamber compliance were also examined. V ̇ O 2 max ( p  < 0.001) and maximal exercise Q ̇ and SV were larger in older trained women compared to the two untrained groups (∼17% and ∼27% for Q ̇ and SV, respectively, versus MU; ∼40% and ∼38% versus OU, all p  < 0.001). Blood volume (mL kg −1 ) and LV mass index (g m −2 ) were larger in OT versus OU (∼11% and ∼16%, respectively, both P  ≤ 0.015) Static LV chamber compliance was greater in OT compared to both untrained groups (median (25–75%): MU: 0.065 (0.049–0.080); OU: 0.085 (0.061–0.138); OT: 0.047 (0.031–0.054), P  ≤ 0.053). Collectively, these findings indicate that lifetime endurance exercise appears to be extremely effective at preserving or even enhancing cardiovascular structure and function with advanced age in women. Key points: The beneficial effects of sustained or lifelong (>25 years) endurance exercise on cardiovascular structure and exercise function have been largely established in men. The current findings indicate that committed (≥4 weekly exercise sessions) lifelong exercise results in substantial benefits in exercise capacity ( V ̇ O 2 max ), cardiovascular function at submaximal and maximal exercise, left ventricular mass and compliance, and blood volume compared to similarly aged or even younger (middle‐age) untrained women. Endurance exercise training should be considered a key strategy to prevent cardiovascular disease with ageing in women as well as men.